Analisis Peran Sarana dan Prasarana Sekolah Terhadap Motivasi Belajar Siswa - Lahagu, Yarni Kristiani; Waruwu, Formal Ode; Laia, David; Harefa, NoveriAmal Jaya (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This article examines the impact of school facilities and infrastructure on students' learning motivation. Student learning motivation is one of the important elements in the success of education but is often hampered by inadequate facilities and infrastructure. This research was conducted at SMP Negeri 5 Botomuzoi using a qualitative approach and a descriptive method. The results of interviews and questionnaires show that the availability of good facilities and infrastructure makes a significant contribution to increasing student learning motivation. This study concludes that investment in school facilities and infrastructure is very important to create a conducive learning environment and increase student learning motivation.